What makes us think? : a neuroscientist and a philosopher argue about ethics, human nature, and the brain - Changeux, Jean-Pierre (Princeton University Press, 2000)
Will understanding our brains help us to know our minds? Or is there an unbridgeable distance between the work of neuroscience and the workings of human consciousness? In a remarkable exchange between neuroscientist Jean-Pierre Changeux and philosopher Paul Ricoeur, this book explores the vexed territory between these divergent approaches--and comes to a deeper, more complex perspective on human nature. Ranging across diverse traditions, from phrenology to PET scans and from Spinoza to Charles Taylor, What Makes Us Think? revolves around a central issue: the relation between the facts (or "what is") of science and the prescriptions (or "what ought to be") of ethics. Changeux and Ricoeur ask: Will neuroscientific knowledge influence our moral conduct? Is a naturally based ethics possible? Pursuing these questions, they attack key topics at the intersection of philosophy and neuroscience: What are the relations between brain states and psychological experience? Between language and truth? Memory and culture? Behavior and action? What is a mental representation? How does a sign relate to what it signifies? How might subjective experience be constructed rather than discovered? And can biological or cultural evolution be considered progressive? Throughout, Changeux and Ricoeur provide unprecedented insight into what neuroscience can--and cannot--tell us about the nature of human experience. Changeux and Ricoeur bring an unusual depth of engagement and breadth of knowledge to each other's subject. In doing so, they make two often hostile disciplines speak to one another in surprising and instructive ways--and speak with all the subtlety and passion of conversation at its very best.